IDENTIFIKASI FAMILI ORCHIDACEAE DIKAWASAN HUTAN LINDUNG DESA SEKENDAL KECAMATAN AIR BESAR KABUPATEN LANDAK - Manik, Firnando; Suryantini, Rosa; Husni, Harnani (JURNAL HUTAN LESTARI, 2017)
The purpose of this research is to know the different types of natural orchids (Orchidaceae) in the area of Sekendal Village protected forest, Air Besar sub-district, Landak District. This research was conducted by using the method of exploration that is placing by the line intentionally or purposive sampling with long trail 1 km and a width of 10 m left, right. Direct orchids identification that done in the field from both the shape of the leaves, stem (bulb), as well as the shape of the flower. From the research results show that at Sekendal Village protected forest has 14 Orchid genus like Agrostophyllum, Bulbophyllum, Coelogyne, Eria, Dipodium, Cerastostylis, Dendrobium, Bromhedia, Liparis, Mycaranthes, Thelasis, Trichotosia, Phalaenopsis. With each track has a different growing place State of the level of epiphyte, litofit or terrestrial. The first path found 8 Orchids genus, second path there are 11 genera are found that have a height of 200-300 m above sea level, the third line of Orchid genus found 4 that all included into the Orchid efipit as for the fourth line is found as many as 10 genus of orchids with an altitude above 300 m above sea level and more leads to secondary forest. From the result of that 4 path there are 14 genera comprising 28 species with a total of 46 individual orchids nature. Keywords: Protected Forest Orchidaceae, purposive, Transect